2001
DOI: 10.1159/000051889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraduodenal Bile on Interdigestive Gastrointestinal and Gallbladder Motility in Healthy Subjects

Abstract: Background/Aims: The enterohepatic circulation of bile acids is related to normal inter-digestive gastrointestinal motility, with the gut peptide motilin also being involved. This study aimed to investigate the effect of intraduodenal artificial bile infusion on antroduodenal and gallbladder motility so as to further elucidate the controlling factors. Methods: Twelve fasting, healthy male volunteers received artificial bile (80 mol% bile acids; 15 mol% phospholipids; 5 mol% cholesterol) or placebo (saline) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
(49 reference statements)
1
10
2
Order By: Relevance
“…13,15 In humans, two previous studies from our group found no effects of intraduodenal bile salt infusions on timing of the various phases of the MMC. 4,5 In contrast, in the present study, ileal infusion of the same mixed micelles led to an earlier appearance of phase III activity. One may hypothesize that ileal rather than duodenal bile salts affect cholinergic influences on small intestinal motility.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…13,15 In humans, two previous studies from our group found no effects of intraduodenal bile salt infusions on timing of the various phases of the MMC. 4,5 In contrast, in the present study, ileal infusion of the same mixed micelles led to an earlier appearance of phase III activity. One may hypothesize that ileal rather than duodenal bile salts affect cholinergic influences on small intestinal motility.…”
Section: Discussioncontrasting
confidence: 92%
“…After biliary diversion in dogs, some investigators have reported unchanged MMC cycling, 14 whereas others reported a loss of MMCs 13,15 . In humans, two previous studies from our group found no effects of intraduodenal bile salt infusions on timing of the various phases of the MMC 4,5 . In contrast, in the present study, ileal infusion of the same mixed micelles led to an earlier appearance of phase III activity.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Our study resembled this association in time, as motilin‐induced gallbladder emptying preceded antral phase III. Based on previous findings with intraduodenal bile infusion, 37 we believe that the appearance of phase III following motilin infusion is the effect of motilin per se , rather than a direct effect of gallbladder excretion into the duodenum. Following motilin‐induced gallbladder emptying, the gallbladder refilled during and immediately after duodenal passage of the motilin‐induced phase III, as has been suggested previously for spontaneous phases III 10 .…”
Section: Discussionmentioning
confidence: 73%